2020
DOI: 10.4049/jimmunol.204.supp.148.5
|View full text |Cite
|
Sign up to set email alerts
|

Human influenza-specific adaptive NK cells mediate potent HLA-E-restricted responses against antigenically distinct influenza strains

Abstract: Novel influenza vaccine approaches to achieve cross-protection against a broad range of antigenically distinct strains are needed. Beyond their ability to eliminate infected cells without the need for prior sensitization, natural killer (NK) cells have been shown to mediate virus-specific recall responses. Notably, exposure to influenza antigens induces protective influenza-specific memory NK cells in mice, but evidence of influenza-specific memory NK cells in humans is still lacking. Using intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Our hypothesis suggests that these molecules play a pivotal role in discerning between self and non-self-peptides. On the other hand, we found that HLA-E and NKG2C are important for the recall responses in aNK cells, which has been earlier reported by us and others in defense against viruses ( 12, 47 ). Moreover, we found e.g., a greater TNFα secretion by aNK cells following a secondary stimulation with specific tumor cells, which facilitates the activation of the transcription factor AP-1 that is activated both in antigen specific T cells and clonal expanded NK cells ( 46, 48 ).…”
Section: Discussionsupporting
confidence: 86%
“…Our hypothesis suggests that these molecules play a pivotal role in discerning between self and non-self-peptides. On the other hand, we found that HLA-E and NKG2C are important for the recall responses in aNK cells, which has been earlier reported by us and others in defense against viruses ( 12, 47 ). Moreover, we found e.g., a greater TNFα secretion by aNK cells following a secondary stimulation with specific tumor cells, which facilitates the activation of the transcription factor AP-1 that is activated both in antigen specific T cells and clonal expanded NK cells ( 46, 48 ).…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, earlier work by Reeves et al showed that memory NK cell responses were observed in Ad26/SIV-vaccinated NHPs [42]. With the recent study by Jost and colleagues confirming that HIV antigen-specific NK cells are found in PLWH, it is plausible that both CTL and NK cell responses could be targeted against more conserved (or potentially ‘networked’), viral peptides on HLA-E [44 ▪▪ ]. Methods to enhance IL-15 signaling during the time of vaccination may be required to ensure proper development of effective HLA-E-restricted CTL responses and boost NK cell activity.…”
Section: Harnessing Immune Cells For Viral Controlmentioning
confidence: 98%
“…This could be supplemented with a STAT5 agonist, HODHBt, which synergizes with IL-15 to enhance activation of HIV-specific T cells [61 ▪ ]. Separately, as the antigen-specific NK cells are KLRG1 + [44 ▪▪ ], blocking this pathway during chronic infection may be a method to further enhnace the expansion and antiviral activity of this NK cell population [21 ▪▪ ], but how this would affect the antigen-specific CTL populations is unknown. Finally, the evaluation of these strategies should consider whether HIV nef would adapt to elicit stronger HLA-E downregulation (as is seen with primary strains of HIV [62]) in response to CTL/NK selective pressure.…”
Section: Harnessing Immune Cells For Viral Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In CMV infection, NKG2Cþ NK cells differentially recognized distinct viral strains, and NKG2C represented a marker of NK cell "memory" [121][122][123]. Chronic HIV-1 infection is associated with higher NKG2C expression on NK cells, indicating that the development of such a pool of adaptive NK cells is possible, and can potentially be exploited for enabling faster and stronger recall responses [13,124,125]. In rhesus macaques, blocking NKG2C signalling diminished HIV-1-specific NK cytolytic activity, while tissuespecific vaccination induced HIV-1-specific recall responses in spite of lower NKG2C expression [15,120].…”
Section: Harnessing Anti-hiv-1 Adaptive Natural Killer Cell Responsesmentioning
confidence: 99%